Peran Guru Mulok Dalam Implementasi Proyek Penguatan Profil Pelajar Pancasila Di Sekolah Dasar - Widiawati, Era Paziroh; Musifuddin, Musifuddin; Parhanuddin, Lalu (Universitas Hamzanwadi, 2024)
This research aims to find out the role of Mulok teachers in implementing the project to strengthen the profile of Pancasila students in elementary schools, what inhibiting factors are experienced by Mulok teachers in implementing the project to strengthen the profile of Pancasila students in elementary schools, and how Mulok teachers try to overcome these factors. obstacles in implementing the project to strengthen the profile of Pancasila students in elementary schools. This research includes qualitative descriptive research. The population of this study were teachers and students at SDN 1 Bungtiang, West Sakra District. The samples for this research were school principals, general teachers, and students. Data collection techniques in this research used observation, interviews, and documentation. Based on the results of data analysis, it was concluded that the role of mulok teachers in implementing the project to strengthen the profile of Pancasila students had not been implemented optimally, they still experienced obstacles in planning activities such as compiling effective teaching modules due to the new curriculum. Lack of support from parents/guardians in project activities to strengthen the profile of Pancasila students. Limited facilities, infrastructure, time and resources mean that project activities to strengthen the profile of Pancasila students cannot be carried out optimally.